Determination of Human NAT2 Acetylator Genotype by Oligonucleotide Ligation Assay - Jeannette Bigler; Chu Chen; John D. Potter (BioTechniques)
The oligonucleotide ligation assay (OLA) was adapted to the genotyping of the N-arylamine-acetyltransferase (NAT2) gene. This assay allows the use of 96-well microplates and robotic workstations for high sample throughput. We found this assay to be accurate, efficient and reliable. Another advantage for epidemiological studies where the DNA supply is limited is the small amount of genomic DNA required. A single PCR with an input of 50–100 ng of genomic DNA provides sufficient amounts of amplified NAT2 fragment to analyze five missense mutations.